2023
DOI: 10.5194/egusphere-egu23-11227
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Detecting Europa’s water plumes with the Particle Environment Package on JUICE

Abstract: <p>The repeated eruptions of water plumes on Europa have been suggested based on Hubble observations, Keck observations and in-situ magnetic field data from Galileo (Roth et al., 2014; Sparks et al., 2016, 2017, 2019; Jia et al., 2018; Arnold et al., 2019; Paganini et al., 2019). The possibility that such plumes could transport material from Europa’s subsurface, or from water reservoirs contained in the ice layer (Vorbuger and Wurz 2021), far above the surface creates an unprecedent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Galileo EPD data are available through NASA's Planetary Data System (PDS) (PDS, 2022). Simulations are available online in Huybrighs et al (2023)…”
Section: Appendix A: Charge Exchange Cross Sectionmentioning
confidence: 99%
“…Galileo EPD data are available through NASA's Planetary Data System (PDS) (PDS, 2022). Simulations are available online in Huybrighs et al (2023)…”
Section: Appendix A: Charge Exchange Cross Sectionmentioning
confidence: 99%
“…The other mismatch to the observation is that the estimated maximum N/S brightness ratio is smaller than that previously observed. To increase the N/S ratio, the deceleration should be even stronger than our assumption (slowdown to 10% of the background plasma flow), while the previous studies indicate that the moon‐plasma interaction may only result in a deceleration down to 40% of the background plasma flow based on the data analysis for the Galileo/PLS in situ observation (Huybrighs, 2019). We confirmed that the slowdown to 40% is not sufficient to reproduce the observed north‐south asymmetry based on the “slow‐down effect” scenario (Figures 5e, 5f, and 5g).…”
Section: Discussionmentioning
confidence: 57%
“…If the convection slows down into less than 10% of the corotation speed, electron accessibility will become lower on the anti‐magnetic‐equator hemisphere, and the north‐south asymmetry will become more pronounced. However, Huybrighs (2019) showed that the plasma convection slows down to 40% of the corotation at Europa based on their model fitting to the Galileo plasma science (PLS) instrument data during the E12 flyby (see Figure 3.16 of Huybrighs (2019)). We estimated the N/S brightness ratio for the case of deceleration into 40% as well and confirmed that the slow‐down rate of 40% is not sufficient to reproduce the systematic change of the N/S brightness ratio based on the “slow‐down effect” scenario (Figure 5f).…”
Section: Discussionmentioning
confidence: 99%